L'enjeu des communautés en sociomusicologie : Le cas du projet de recherche sur le développement des publics de la musique au Québec - Marcoux-Gendron, Caroline; Couture, Ariane; Gervasi, Flavia; Duchesneau, Michel (MUSICultures, 2015)
The basis of this article arises from the project “Développement des publics de la musique au Québec” (DPMQ), developed by the sociomusicology research team at the Observatoire interdisciplinaire de création et de recherche en musique (OICRM) in partnership with nine musical organizations in Quebec. Our first research question involves interrogating the definition of “community” (or “communities”), and this article proposes an application of this concept in line with the objectives of the DPMQ: establishing a social map of audience attendance and numbers of musical amateurs in Quebec, and experimenting with new forms of musical mediation in collaboration with professional partners who will apply them within the context of their activities. The second question concerns the difficulty of reconciling different work “cultures” between researchers and professionals in the cultural realm. The question in simple terms, therefore, is how to overcome the absence of a tradition of research among community partners? The third question emerges from the previous question: how to resolve the issue of sharing information? We approach these three sociomusicological research questions with respect to our initial experiences with two community partners: la Société de musique contemporaine du Québec (SMCQ) and the Festival du monde arabe (FMA).